Effect of digestible protein on intermediate metabolism, hepatic enzyme activities, energy reserves, and growth performance of pacu (Piaractus mesopotamicus) in the finishing growth phase - Oshiro, Amanda Miyuki [UNESP]; Khan, Kifayat Ullah [UNESP]; Carli, Gabriela Castellani [UNESP]; Pahor-Filho, Eduardo [UNESP]; Sakomura, Nilva Kazue [UNESP]; Fernandes, João Batista Kochenborger [UNESP]; Takahashi, Leonardo Susumu [UNESP] (My University, 2024)
This study investigated the effect of different levels of digestible protein (DP) on blood metabolites, hepatic enzyme activity of glycolysis and amino acid metabolism, energy reserves, and the production characteristics of pacu (Piaractus mesopotamicus) during the finishing growth phase. Six semi purified and isoenergetic diets, containing 16.3, 20.1, 23.8, 27.2, 31.5, and 34.8% of balanced DP, provided with essential amino acid balance, were hand-fed to pacu (1100.0 ± 10.3 g, initial weight) three times daily for 7 weeks. The experiment consisted of six treatments, with three randomly arranged replicates (tanks) per treatment. The data obtained from this experiment were analyzed by one-way analysis of variance (ANOVA), and significant differences (p < 0.05) between treatments were determined using Tukey’s test. Blood metabolites, except serum ammonia and the hepatic enzymes activities of glycolysis and amino acid metabolism, except hexokinase activity were affected (p < 0.05) by balanced DP. The energy reserve indices, except hepatic total lipid content, were also found associated (p < 0.05) with balanced DP. The test diets significantly (p < 0.05) affected growth performance parameters. Higher dietary proteins led to a greater energy uptake by fish from the protein in feed. Overall, fish fed the intermediate level (23.8%) of balanced DP with digestible energy of 17.95 MJ kg−1 showed better production traits and physio-biochemical health markers. This information could help nutritionists and farmers to develop nutritionally balanced and economically and environmentally sustainable aquafeed for promoting healthy and sustainable production of pacu in intensive culture systems.
Keywords: Healthy aquafeed; Macronutrient; Nutritional physiology; Sustainability